Evaluating use and outcomes of mobility technology: A multiple stakeholder analysis. (July 2013) - Hammel, Joy; Southall, Kenneth; Jutai, Jeffrey; Finlayson, Marcia; Kashindi, Gabriel; Fok, Daniel
<x xml:space="preserve">Abstract</x> Purpose: This qualitative, multi-site study compared and contrasted the outcomes of mobility technology (MT) and the factors influencing these outcomes from the perspective of MT users, caregivers, and professionals involved in MT service delivery. Method: Qualitative focus groups were held in the USA and Canada with multiple stakeholder groups (consumer: n = 45, caregiver: n = 10, service provider: n = 10). Data were analyzed thematically. Results: MT outcomes were conceptualized by participants as a match between expectations for MT and the actual outcomes experienced. Several factors influenced the match including a) MT features, b) environmental factors (e.g. built/physical environment, societal context of acceptance, MT delivery systems/policies), and c) the ability to self-manage the interaction across person, technology and environment, which involved constant negotiation and strategizing. Stakeholders identified MT outcomes that corresponded to ICF levels including body structure and function, activity, and participation across environments; however, varied on their importance and influence on MT impact. Conclusions: The conceptual fit model and factors related to self-management of MT represent new knowledge and provide a framework for stakeholder-based evaluation of MT outcomes. Implications for MT assessment, service delivery, outcomes research, and interventions are discussed.